Experimental study on effect of spires on the lateral nonuniformity of mean flow in a wind tunnel - Nurizzatul Atikha, Rahmat; Hagishima, Aya; Ikegaya, Naoki; Tanimoto, Jun (Novel Carbon Resource Sciences, 2018)
The present work discusses in detail the experimental settings to establish a thick artificially generated urban-like atmospheric boundary layer in a short-fetch-length wind tunnel. It summarizes the comprehensive review of past studies on the flow behind quarter-elliptic-wedge spires, and clarifies the current issue of the spire setting in a wind tunnel experiment. This study investigates the persistent spanwise heterogeneity, the spatial structures of the flow past a row of quarter-elliptic-wedge spires, the streamwise distance required for a wake of elliptic-wedge spires to naturally recover, and how the mean flow changes farther downstream. Two experimental conditions were implemented in the present work (without and with spires) to analyse the effect of mean flow heterogeneity both within and above boundary layer height (BLH) regions, developing over a smooth wall that was produced by the installation of a flat plate on the wind tunnel floor.